How to Establish a Minimal Invasive and Stable Carotid Artery Stenosis Rabbit Model? A Simple and Effective Carotid Artery Balloon Strain Technique - Liu, Zhengli; Gong, Maofeng; Zhao, Boxiang; Gu, Jianping; Su, Haobo; Zhou, Yangyi; Fu, Guanqi; He, Xu; Kong, Jie (Frontiers in Physiology, 2021)
Background: The purpose of this study is to establish a minimal invasive technique to create a stable carotid artery stenosis rabbit model. This article summarizes the specific methods and key points of this technology. Methods: The rabbit was anesthetized through the vein. After the femoral artery was exposed, a minimally invasive needle was used to puncture the femoral artery, then the sheath was placed into the artery. We firstly put catheter in the ascending aorta for angiography, and then use PT2 guide wire for super-selection. The PT2 guide wire was retained, and a balloon was placed in the right common carotid artery(CCA) through guide wire to inflate it for three times. Six rabbits in 2W group and 4W group were examined at 14 and 28 days respectively. Results: All the 18 animals were survived and observed. The rabbits in the 2W and 4W groups showed stenosis of the right CCA. DSA showed the diameter was lower than that in the con group(1.04±0.10mm, 0.71±0.12mm and 1.83±0.08mm in 2W, 4W and con group, P<0.05). Pathology also suggested carotid stenosis and obvious intimal hyperplasia. The results of immunohistochemistry showed that α-SMA was highly expressed in the 2W and 4W groups, and the integrated optical density (IOD) value was higher than that in the con group(14807.11±1822.30, 22245.96±1212.82 and 6537.16±1186.62 in the 2W, 4W and con group, P<0.05). Meanwhile, CD31 was low expressed in the 2W and 4W groups, and the IOD value was lower than that in the con group (519.14±44.40, 1029.64±98.48, and 1502.05±88.79 in the 2W, 4W and con group, P<0.05), which suggests endothelial damage and partial repair. IFlow showed the time-to-peak after balloon strain in the 2W and 4W groups was longer than that in the con group. Conclusion: We establish a minimal invasive, effective and safe method to establish a carotid artery stenosis rabbit model. The highlights of this technology are the application of minimally invasive methods, reducing surgical bleeding, infection and related complications. This technology avoids the influence of tissue around CCA in traditional carotid artery balloon injury model, which may lead to more accurate treatment outcomes.